Evaluation of Outcome of Upper Ureteric Stone Management by ESWL: A Study in Dhaka, Bangladesh (Bangladesh Journal of Endosurgery, 2014)
Objective: To evaluate the outcome of extracorporeal shock wave lithotripsy  (ESWL) for the management of upper ureteral stones.Materials and methods: This prospective observational study assessed 42 patients who underwent ESWL  from March 1, 2009 to June 30, 2010 in the National Institute of Kidney Diseases  and Urology, Dhaka. The stone size, success rate, and postoperative complications  were evaluated. A successful outcome was defined as the patient being stone-free  on radiography 1 month after treatment.Results: Out of 42 patients, 34 had stone  size more than 1 cm and the remaining had stone size less than 1 cm. Stone clearance  rate after single session was 36 (85.7%). Immediate complications included  fever in 14 and severe hematuria in 6 patients. Almost 50% developed urinary tract  infection, and steinstrasse was observed in 2 patients. More than 90% of the  patients exhibited complete clearance of stone after single session after 3 months of  intervention. There was no ureteral injury and no patient developed stricture.Conclusion: For management of selective sized upper ureteric stone, ESWL is  superior to other minimally invasive procedures like ureterorenoscopy + intracorporeal  pneumatic lithotripsy (ICPL) considering greater stone clearance, less  complications, and non-invasivenessDOI: http://dx.doi.org/10.11593/bje.2013.0103.0020Bangladesh Journal of Endosurgery Vol.1(3) September 2013: 13-15